PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING PADA MATERI LISTRIK DINAMIS UNTUK MENINGKATKAN KETERAMPILAN GENERIK SAINS SISWA KELAS X SMAN 1 TAMBUSAI UTARA - Sri Wahyuni; M. Rahmad '; Muhammad Nasir (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aimed to describe and differentiate the generic science skills students who learn with creative problem solving learning models with a group of students who studied with conventional learning. The method used in this research is a quasi-experimental research design with intact group comparison design. The population in this study were all students of class X SMA Negeri 1 North Tambusai second semester of the school year 2015/2016 there consist of seven classes with enrollment of 256 students. The research sample was set at 2 classes with 70 students, which is determined by simple random sampling technique. Data collected by using generic science test. Analysis of the data in this study was a desciprtive analysis and inferential analysis. Descriptive analysis was used to determine the generic science skills students. The inferential analysis was used differentiate a generic science skills considerably using independent samples t-test. The analysis data shows that the average percentage of generic science skills 55.73% with a low category and 47.40% for the control group with very low category. The value of t-test is tcount = 2,391, ttable = 1,66691, p = 0,02 means tcount > ttable dan p < 0,05, then Ho is rejected. Which means there is a difference significant generic science skills among students who learn by using a model of creative problem solving with students learning with conventional learning with the results of This means that the generic science skills students learn with creative problem solving models better than students learning with conventional learning.Key Words: Generic science skill, creative problem solving, dynamic electrical